RISK MANAGEMENT IN BANKS: NEW APPROACHES TO RISK ASSESSMENT AND INFORMATION SUPPORT - Chornous, Galyna; Ursulenko, Ganna (Ekonomika, 2013)
Abstract. This study is devoted to the problems of improving the banking risk management, taking into account the new regulatory and technological requirements based on the use of modern technology and combining the latest achievements in artificial intelligence, numerical mathematics, statistics and information technology. The paper analyzes the characteristics of banking risks, the main methods of assessment used in practice. The authors propose new prospective approaches to assessment, based on the most modern methods of data analysis, identify prospective directions for banking information system improvement and suggest the possibility of their implementation. The example of Ukrainian banks shows the main problems of using new approaches to risk assessment and its information support. The article proposes the ways to overcome them. Key words: banking risk management, artificial intelligence, banking risks estimation, data analysis